2014
DOI: 10.1037/a0036373
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood disorder, spiritual well-being, and parenting stress in African American women.

Abstract: Using a culturally-informed risk-protective framework, the purpose of this study was to examine spiritual well-being (existential, religious) as a moderator (protective factor) in the relation between neighborhood disorder (risk factor) and parenting stress in among a high risk sample of low-socioeconomic status (SES), African American women (N = 144). These women, who were primary caregivers of children aged between 8 and 12 reported on disorder in their existential and religious well-being, neighborhoods, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 91 publications
1
32
0
Order By: Relevance
“…These findings suggest that adults with BD who experienced sexual abuse in childhood were less likely than those without CSA to report a strong sense of meaning and purpose in life, but neither more nor less likely to report a stronger belief in God. These findings are interesting in the context of recent research that found similar results (Lamis, Wilson, Shahane, et al., ; Lamis, Wilson, Tarantino, et al., ). A review by Walker, Reid, O'neill, and Brown () concluded that although the majority of studies on the association between childhood abuse and religiosity/spirituality report a decline in religiosity and/or spirituality following childhood abuse, the nature of this relationship is nuanced (Walker et al., ) and likely complicated by other factors (e.g., social support; cultural relevance of religiosity).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These findings suggest that adults with BD who experienced sexual abuse in childhood were less likely than those without CSA to report a strong sense of meaning and purpose in life, but neither more nor less likely to report a stronger belief in God. These findings are interesting in the context of recent research that found similar results (Lamis, Wilson, Shahane, et al., ; Lamis, Wilson, Tarantino, et al., ). A review by Walker, Reid, O'neill, and Brown () concluded that although the majority of studies on the association between childhood abuse and religiosity/spirituality report a decline in religiosity and/or spirituality following childhood abuse, the nature of this relationship is nuanced (Walker et al., ) and likely complicated by other factors (e.g., social support; cultural relevance of religiosity).…”
Section: Discussionsupporting
confidence: 85%
“…With research in this area burgeoning, the differential effects of EWB and RWB are being increasingly investigated, and more recent studies suggest a greater role for EWB in positive psychological outcomes than RWB. For instance, EWB is associated with improved quality of life, better psychological adjustment, and lower levels of hopelessness, despair, and suicidal ideation/behavior in a variety of patient populations (Edmondson, Park, Blank, Fenster, & Mills, ; Fischer et al., ; Kleftaras & Katsogianni, ; Lamis, Wilson, Shahane, & Kaslow, ; Lamis, Wilson, Tarantino, Lansford, & Kaslow, ). In relation to BD, however, there appears to be limited research addressing the influence of religiosity/spirituality on different aspects of the illness.…”
mentioning
confidence: 99%
“…In another study, one conducted specifically in pregnant women, SR was strongly and inversely related to stress and anxiety (Breen et al 2006). Finally, Lamis and colleagues found that parenting stress was lower among the women who scored high on spiritual well-being (Lamis et al 2014). The DSES was also able to distinguish various subgroups of women in this study (known-groups comparison).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies20,21,3941 have shown that good bonding and communication between parents and young individuals delay the age of the adolescent’s sexual debut, reduce the likelihood of risky sexual behaviors, and lower the risk of contracting STDs/HIV. Other social contexts around the young individuals, such as peers and people in the neighborhood, also play an essential role in modifying the young individuals’ sexual behavior 34,4247. In fact, the norms created by peers and the safety of the neighborhood have increasing influence compared to family members on the adolescent’s behavioral development as the individual gets older.…”
Section: Introductionmentioning
confidence: 99%